Complexation of malic acid with cadmium(II) probed by electrospray ionization mass spectrometry - Jaklová Dytrtová, Jana; Jakl, Michal; Schröder, Detlef (Talanta, 2012)
Electrospray ionization was used as a technique for the characterization of the interactions between cadmium(II) ions and malic acid (1) in aqueous solution. Particular attention was paid to the nature of the species formed, which generally correspond to complexes of CdX(+) cations with neutral malic acid, where X either is the counterion of the metal salt used as a precursor (i.e. X=Cl, I) or corresponds to singly deprotonated malic acid. In pure water solutions, also highly coordinated complexes [Cd(1-H)(1)(2)](+) and [CdCl(1)(2)](+) were detected, whereas the most abundant complexes detected in a sample of soil solution were: [Cd(1-H)(1)](+) and [CdCl(1)](+). With respect to possible application in environmental analysis, the effects of (i) metal salts present in solution, (ii) modest mineralization, and (iii) the matrices of real soil solutions were probed. While the presence of other metals leads to additional complexes, the characteristic species containing both cadmium(II) and malic acid can still be detected with good sensitivity.
Keywords: hmotnostní spektrometrie s elektrosprejovou ionizací; Malates; kadmium; maláty; Spectrometry, Mass, Electrospray Ionization; Cadmium